Effect of magnetic and electric fields on optical properties of semiconductor spherical layer - Holovatsky, V.A.; Bernik, I.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Theoretical investigation of the influence of magnetic and electric fields on the
energy spectrum and wave functions of electron in semiconductor spherical layer has
been performed. The case of co-directed electric and magnetic fields has been
considered. The Schrödinger equation has been solved using the method of expansion for
the wave function of electron in the spherical layer under external fields by applying the
complete set of wave functions of a quasi-particle in a spherical nanostructure without
the external fields. It has been shown that electric and magnetic fields take off the
spectrum degeneration with respect to the magnetic quantum number. The external fields
rebuild the energy spectrum and deform wave functions of electron. Moreover, their
influence on the spherically symmetric state is the largest one. Increasing the magnetic
field induction entails a monotonous dependence of the electron energy for the states
with m > 0 and non-monotonous one for the states with m < 0. The ground state of
electron is successively formed by the states with m = 0, –1, –2, … with increasing the
induction of magnetic field. The enhancement of the electric field mainly diminishes the
electron energy. The influence of field on the energy and intensities of the 1p-1s
intraband transition has been studied. It has been shown that there exists a certain value
of the electric field, at which the energy of quantum transition doesn’t depend on the
magnetic field induction.